Comparison between Laparoscopy and Laparotomy in the Management of Ectopic Pregnancy - Tania Akbar,; Sumia Bari,; Sheuly Begum,; Rina Nasrin,; Monowara Begum, (Journal of Enam Medical College, 2024)
Introduction: Ectopic pregnancy has become one of the most alarming causes of maternal mortality and morbidity and the number of maternal death due to ectopic pregnancy is also in increasing trend. Usually ruptured ectopic pregnancy is managed by laparotomy. But nowadays due to improved anesthesia and cardiovascular monitoring support together with advanced laparoscopic surgical skills and experience, operative laparoscopy for surgical management of ectopic pregnancy is justified, even in women with significant hemoperitoneum. Objectives: The aim of this study was to assess the clinical profile, risk factors and diagnostic modalities for ectopic pregnancy and to assess the operative findings, operative procedure and post-operative condition at laparoscopy and laparotomy cases. Materials and Methods: It was a cross-sectional study, conducted in the Department of Obstetrics & Gynecology in Enam Medical College & Hospital, Dhaka, Bangladesh. The study period was from July 2018 to July 2020. A total 72 patients were included for the study. All the patients were managed according to the hospital protocol. Data were analyzed by using Statistical Package for Social Sciences (SPSS) version 11.5. Results: A total of 72 cases were the study subjects. Laparotomy was done in 45 (62.5%) cases and laparoscopy in 27 (37.5%) cases. Most of the patients came with abdominal pain. Twenty seven patients (37.5%) who came with shock and all were managed by laparotomy. Commonest site of ectopic pregnancy was ampullary region －27 (37.5%) and were managed by laparotomy and 23 (31.94%) by laparoscopy. Most of the ectopic pregnancies were ruptured and 14 (19.44%) ruptured cases were managed laparoscopically. Hemoperitoneum (1000－2000 mL) was present in 25 cases, among them 7 (9.72%) were managed by laparoscopy. Salpingectomy was the commonest surgery－by laparoscopy 26 (36.11%) and by laparotomy 42 (58.38%). In laparotomy 32 (44.44%) cases and in laparoscopy 9 (12.5%) cases needed blood transfusion, which was comparatively less in laparoscopy. There was no wound infection in laparoscopy cases. Post-operative morbidity was also less in laparoscopy than in laparotomy. Conclusion: Ectopic pregnancy is considered as a life-threatening severe health condition and the number is dramatically increasing day by day. For the treatment of ectopic pregnancy, emergency intervention is must. Nowadays, laparoscopic management might be the most effective procedure with maximal safety and efficacy. J Enam Med Col 2022; 12(2): 84−89